Maxim violations and their reasons in an animated movie: a Gricean approach to communication - Arbain, Arbain; Geroda, Godefridus Bali; Mulyono, Enno Audina (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2023)
This study analyzes the utterances of maxim violation produced by characters in the 2022 animated film, Puss in Boots: The Last Wish, as well as the motivations underlying them. Using a qualitative research method, content analysis techniques are used to conduct the analysis. The analysis adopted Grice's Cooperation Principle, which incorporates Grice's Maxims, and their violation, as well as additional hypotheses from other experts regarding the rationale for such violations. To support the analysis, this research involved an expert in the pragmatic field specially to provide analysis related to the types of maxims used and the reasons for using these maxims. This study uncovered a total of 51 utterances of maxim violations in the characters’ talks. They can be categorized as the violations of the following maxims: 21 (41.1%) of quality, 16 (31.3%) of quantity, 7 (13.7%) of manner, and 6 (11.7%) of relevance. There are six types of reasons for using maxims violations, namely communicating personal interests, Avoiding discussion, Pleasing interlocutors, Saving face, Misleading listeners, Extending answers. The characters violated the maxims in a variety of contexts and for a variety of reasons, but primarily out of a wish to express their individual self-interests.